Examination of Hippocampal Differences Between Alzheimer Disease, Amnestic Mild Cognitive Impairment and Normal Aging: Diffusion Kurtosis - Wang, Dan; Guo, Zhao-Hui; Liu, Xing-Han; Li, Yue-Hua; Wang, He (Current Alzheimer Research, 2015)
Purpose: To examine hippocampal differences between Alzheimer disease (AD), amnestic mild cognitive impairment (aMCI) and normal aging. Materials and methods: This study was approved by the local ethics review board, and informed consent was obtained from volunteers/guardians. The study comprised 60 subjects: 20 aMCI patients, 20 AD patients and 20 normal controls (NC group). Magnetic resonance imaging and diffusion kurtosis imaging of the hippocampus were performed. Nonlinear fitting routines and equations were used to calculate mean diffusion (MD) and mean kurtosis (MK). Analysis of variance was used to compare the bilateral MK/MD values/volumes of the hippocampus for the three groups using the Fisher least significant difference test (a two-sample t-test comparison). Pearson correlation coefficients were calculated for the correlations between mini-mental state examination (MMSE) scores and MK/MD values/volumes. Results: There were significant differences between the AD and NC groups and between the AD and aMCI groups in terms of normalized bilateral hippocampal volume. There were significant differences between the NC, aMCI and AD groups in terms of both right and left hippocampus MK values. For the right hippocampus MD values, there was a significant difference between the NC and AD groups. For the left hippocampus MD values, there were significant differences between the AD and NC groups and between the AD and aMCI groups. Pearson correlation coefficients for all correlations between MMSE scores and hippocampus MK/MD values/volumes were significant. Conclusion: The bilateral hippocampal MK/MD values may be more sensitive than volumes in the diagnosis of aMCI and AD patients.
Keywords: diffusion kurtosis imaging